2019
DOI: 10.1177/0034644619885348
|View full text |Cite
|
Sign up to set email alerts
|

Does Remittance Inflow Granger-Cause Economic Growth in South Africa? A Dynamic Multivariate Causality Test

Abstract: In this study, we examine the dynamic causal relationship between remittances and economic growth in South Africa during the period from 1970 to 2017. Although South Africa is well-known for being a source of cross-border remittances to various countries, especially in the African continent, remittance inflows to South Africa have grown in the recent past. The growth in remittances, on one hand, and the need to fight against poverty and inequality in South Africa and ultimately improve economic growth, on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…On the other hand, there are a number of studies that reveal bi-directional causality between the variables, meaning that causality is running both directions (Jouini, 2015;Ahmed and Hakim, 2017;Kumar and Vu, 2014 etc. ) Contrary, Nyasha et al (2020) find that there is no evidence of causality, neither in the short-run nor in the long-run between remittances and growth in the case of South Africa over the period 1970 to 2017. The literature provides inconclusive results as it pertains to the direction of causality between remittances and growth.…”
Section: Literature Reviewcontrasting
confidence: 81%
“…On the other hand, there are a number of studies that reveal bi-directional causality between the variables, meaning that causality is running both directions (Jouini, 2015;Ahmed and Hakim, 2017;Kumar and Vu, 2014 etc. ) Contrary, Nyasha et al (2020) find that there is no evidence of causality, neither in the short-run nor in the long-run between remittances and growth in the case of South Africa over the period 1970 to 2017. The literature provides inconclusive results as it pertains to the direction of causality between remittances and growth.…”
Section: Literature Reviewcontrasting
confidence: 81%
“…Studies examining the impact of remittances on poverty and economic growth have received much attention since the surge in remittance inflows, especially in low-and middle-income countries, albeit the findings on the causality between remittances and poverty are inconclusive: some confirm a unidirectional causal relationship between the two (see: Azam, Haseeb & Samsudin, 2016) others found a bidirectional causal relationship (Azam, Haseeb & Samsudin, 2016;Yasmin et al, 2015;Gaaliche & Gaaliche, 2014;Hatemi-j & Uddin, 2014), while yet others found no causality (Azam, Haseeb & Samsudin, 2016). The same applies to studies that investigated the causality between remittances and economic growth (Depken, Niksic Radic & Paleka, 2021;Jouini, Mabrouk & Mim, 2021;Nyasha & Odhiambo, 2020). Some researchers have taken a step further and investigated the causal relationship between remittances, economic growth, and poverty in the same study (Abduvaliev & Bustillo, 2020).…”
Section: Review Of Relevant Literaturementioning
confidence: 97%
“…Using vector autoregressive models and Granger causality test, the study found a unidirectional causal link between remittances and economic growth (Depken, Niksic Radic & Radeka, 2021). In the same spirit, Nyasha and Odhiambo (2020) analysed the causal relationship between remittances and economic growth using data from 1970 to 2017. Employing an ARDL approach within a multivariate Granger causality framework, the study found no causal relationship between the two (Nyasha & Odhiambo, 2020).…”
Section: Remittances and Economic Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study of the impact of remittances in Indonesia, Adams and Cuecuecha (2010) stated that recipients of remittances are poorer than nonrecipient households as recipients engage in more consumption at the margin rather than investing in productive assets. Nyasha and Odhiambo (2020), examining economic growth in South Africa, conclude that there is no causal relationship between remittances and economic growth in South Africa, while Ahmed and Hakim (2017) conclude that "a long-run bidirectional relationship exists between remittances and economic growth in Togo. "…”
Section: Literature Reviewmentioning
confidence: 99%